Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.metabol.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in dietary carbohydrate-lipid exposure regulate expression of the non-alcoholic fatty liver disease-associated gene PNPLA3/adiponutrin in mouse liver and HepG2 human liver cells

Abstract: Objective Patatin-like phospholipase domain containing 3 (PNPLA3, adiponutrin) has been identified as a modifier of lipid metabolism. To better understand the physiological role of PNPLA3/adiponutrin, we have investigated its regulation in intact mice and human hepatocytes under various nutritional/metabolic conditions. Material/Methods PNPLA3 gene expression was determined by real-time PCR in liver of C57BL/6 mice after dietary treatments and in HepG2 cells exposed to various nutritional/metabolic stimuli. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…This differential activation of signaling networks in NASH and SS versus NOR specimens suggests a central role for these carbohydrate metabolism phosphosites in mediating the disease processes driving the development of NASH. These are consistent with recent findings examining the role of polymorphisms in patatin‐like phospholipase domain containing3 (PNPLA3), strongly associated with NAFLD in humans, which showed that excess carbohydrate relative to fat potently regulates PNPLA3 . More work is needed to fully understand how aberrant carbohydrate metabolism drives NAFLD progression.…”
Section: Discussionsupporting
confidence: 88%
“…This differential activation of signaling networks in NASH and SS versus NOR specimens suggests a central role for these carbohydrate metabolism phosphosites in mediating the disease processes driving the development of NASH. These are consistent with recent findings examining the role of polymorphisms in patatin‐like phospholipase domain containing3 (PNPLA3), strongly associated with NAFLD in humans, which showed that excess carbohydrate relative to fat potently regulates PNPLA3 . More work is needed to fully understand how aberrant carbohydrate metabolism drives NAFLD progression.…”
Section: Discussionsupporting
confidence: 88%
“…Because PNPLA3 has previously been reported to influence lipid metabolism in animal models and in in vitro studies [ 40 , 41 ], we evaluated the interplay of PNPLA3 liver expression with the expression of the main lipid metabolism-related genes. In the current first human study in this sense, PNPLA3 expression positively correlated with LXRα , PPARα , and SREBP2 liver expression.…”
Section: Discussionmentioning
confidence: 99%
“…HepG2 cells (ATCC, Manassas, VA, U.S.A.) were cultured in 79% Dulbecco’s modified Eagle’s medium (DMEM, 10569044, Gibco, Waltham, MA, U.S.A.) that contained 20% FBS (10099-141, Gibco) and 1% penicillin-streptomycin (100 U/ml, 15140-122, Gibco) [ 24 ]. Other groups of HepG2 cells were cultured in medium that contained a 1% long chain fat emulsion (0338-0519-48, Intralipid® 20%, Baxter, Deerfield, IL, U.S.A.) for 48 h; those cells were used to construct the NAFLD cell model [ 25 ]. Next, the cells were treated with either CHLZT-containing serum (defined as Compound-S) or AICAR-containing serum (defined as AICAR-S) at final concentrations of 20%.…”
Section: Methodsmentioning
confidence: 99%